Realms of Memory of the First Ukrainian Political Emigrants: On the Example of P.Orlyk (1710–1720) - Кононенко, Василь (Український історичний журнал, 2022)
The aim of the article. The investigation deals with study of the realms of memory of the first Ukrainian political émigré representatives (in the first half of the 18th century) on the example of the hetman in exile, Pylyp Orlyk. Realms of memory (lieux de mémoire) are shown as structural elements from which Ukrainian identity was formed at that time. The research is based on historical documents that belonged to P.Orlyk or were written with his participation. In the article is to reconstruct the realms of memory of political emigrants (on the example of P.Orlyk). The article uses the methodology of historical science, primarily the analysis of specific lieux de mémoire. The scientific novelty of the article is the analysis of Cossack realms of memory, which became the basis for the development of Ukrainian identity at that time. Conclusions. The article highlights examples of such realms of memory: territory, cities, rivers, historical heroes, elements of political system, visual lieux de mémoire. Kyiv is shown as an example of the city that established as a key Cossack realm of memory and influenced the Ukrainian identity. Personality of B.Khmelnytskyi is considered as a lieu de mémoire that played an important role in various forms of Ukrainian identity. The Rights and Freedoms and the institution of the general treasurer (pidskarbii) were studied as realms of memory that determined the political values of Cossack society. Cossack Regalia (kleinody) are depicted as a visual expression of Cossack values and identity.